The Disability Divide: a study into the impact of computing and internet-related technologies on people who are blind or vision-impaired - Hollier, Scott (Curtin University, 2006)
People with disabilities, and in particular people who are blind or vision impaired, are not embracing computing and Internet-related technologies at the same rate as the able-bodied population. The purpose of this study was to find the reasons behind this digital divide for people with disabilities and provide solutions. The investigation into this 'disability divide' initially examined the historical significance of the social construction of disability, the developments of computing and Internet-related technologies and the evolution of associated government and corporate policies. In order to gain an understanding of the specific elements in the current disability divide, interviews were conducted with a range of government representatives, multinational information technology developers and online information providers in Australia and the United States of America. In order to gain an understanding of what people with disabilities required from information technology, a national survey was conducted with people who are blind or vision impaired to determine their computing and Internet experiences. This study clearly identified that people with vision disabilities have a high level of computing and Internet expertise and it is specific barriers, rather than lack of will, that has prevented access to computing and Internet-related technologies. These barriers include issues relating to the perception of disability in society, Federal and state government policy, corporate policy, mainstream computing products, assistive technologies, real-time online communication, poverty and a lack of educational opportunities. Addressing the issues in these areas will significantly reduce the impact of the disability divide, allowing people who are blind or vision impaired to participate more effectively in the information age.